Influence of photodynamically inactivated Pseudomonas aeruginosa vaccine on cytokine secretion by mouse dendritic cells - Dercach, Svitlana; Martynov, Artur; Gorodnitskaya, Natalia; Kutsay, Nataliya; Romanova, Helen (Annals of Mechnikov's Institute, 2022)
Іntroduction. The article is devoted to study of the immunostimulating properties of the Pseudomonas aeruginosa vaccine, developed by the authors, obtained using the photodynamic method of bacteria inactivation (PHI). The data confirming the effect of this vaccine on the secretion of a number cytokines are presented. The ability of PHI through stimulating dendritic cells significantly activate the cellular link of the immune system in experimental animals with the Pseudomonas aeruginosa infection. Materials and methods. The total number of animals in our study was 60 male mice weighing 18-20 g, 10 mice per group. The following groups of animals were formed: 1. Vaccinated with heat-inactivated (THI) P. aeruginosa vaccine; 2. Vaccinated with photodynamically inactivated (FIO) P. aeruginosa vaccine; 3. TIS vaccinated with P. aeruginosa + infection; 4. VIV vaccinated with P. aeruginosa + infection; 5. Intact animals; 6. Intact infected animals. Determination of the cytokines level in bone marrow dendritic cells (BMC) in their cultivation medium: the concentration of cytokines in the supernatants of mouse dendritic cells was determined by enzyme immunoassay on the Stat Fax 2100. The content of 8 cytokines (IL-1α, IL-4, IL-4 , IL- 12, IL-13, IL-17A, IFN-γ) using the Bio-Plex Pro™ Mouse Cytokine 23-plex Assay (BioRad, USA) according to the manufacturer's instructions. Results and discussion. As a result of the studies, it was found that the UV/VIS- inactivated vaccine against P. aeruginosa, in the presence of riboflavin and vikasol, which was vaccinated with infected experimental animals, most contributed to the increase in secretion of a wide range cytokines. on the subsequent stages of the development of the immune response, including the polarization of T-helpers in comparison with the thermally inactivated vaccine. In the studies course, the secretion of pro-inflammatory, Th1- and Th2-cytokines by dendritic cells was observed, while the content of cytokines that promote formation of Th1-lymphocytes increased more strongly. Findings. An experimental study confirms the ability of the killed Pseudomonas aeruginosa vaccine (FIO) obtained by the latest method to effectively activate the cellular link of the innate immune system due to dendritic cells, which are antigen-presenting cells. Keywords: Pseudomonas aeruginosa vaccine, cytokine cellular immunity, dendritic cells. DOI: 10.5281/zenodo.6634832